Site-specific identification and quantitation of endogenous SUMO modifications under native conditions - Ryan J. Lumpkin (Nature Portfolio, 2017)
SUMOylation is post-translational modification implicated in several biological pathways. Here the authors describe an approach for the global profiling of SUMO attachment sites under native conditions that also allows the parallel determination of SUMO and Ub attachments.